2022
DOI: 10.1108/ijchm-01-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Linking environmental knowledge, environmental responsibility, altruism, and intention toward green hotels through ecocentric and anthropocentric attitudes

Abstract: Purpose This study aims to examine the effects of environmental knowledge, perceived environmental responsibility and altruism on tourist’s intention to stay in green hotels. In addition, the mediating role played by tourists’ attitudes, including ecocentric and anthropocentric attitudes, is explored. Design/methodology/approach Data were collected from 393 international tourists in Malaysia. This study followed a cross-sectional approach and applied the partial least squares – structural equation modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 87 publications
(183 reference statements)
0
35
0
1
Order By: Relevance
“…The NEP is most often used to measure ecological worldview (Milfont and Duckitt, 2010), which is also known as explicit environmental attitude (Wang et al, 2023). Individuals who scored high in NEP values (Levine and Strube, 2012) with an explicit environmental attitude will show high interest in social, political, and other issues relating to the protection of the natural environment, and will offer various possible solutions for those issues (Patwary et al, 2022). Individuals with an explicit environmental attitude can also exhibit different types of pro-environmental behavior that can have a direct effect on public policy-making, such as being a member of an environmental group, but also have an indirect effect on the natural environment, like developing new policies on environmental preservation (Leonidou et al, 2010).…”
Section: Explicit Environmental Attitude Toward Personal Norm and Int...mentioning
confidence: 99%
See 2 more Smart Citations
“…The NEP is most often used to measure ecological worldview (Milfont and Duckitt, 2010), which is also known as explicit environmental attitude (Wang et al, 2023). Individuals who scored high in NEP values (Levine and Strube, 2012) with an explicit environmental attitude will show high interest in social, political, and other issues relating to the protection of the natural environment, and will offer various possible solutions for those issues (Patwary et al, 2022). Individuals with an explicit environmental attitude can also exhibit different types of pro-environmental behavior that can have a direct effect on public policy-making, such as being a member of an environmental group, but also have an indirect effect on the natural environment, like developing new policies on environmental preservation (Leonidou et al, 2010).…”
Section: Explicit Environmental Attitude Toward Personal Norm and Int...mentioning
confidence: 99%
“…As the hospitality industry consume a great deal of energy and resources that negatively impact the environment (Ahmad et al, 2021), hotels need to implement green strategies to maintain competitiveness in the hospitality marketplace (Wang et al, 2020a), as they are able to charge higher rates to consumers who are willing to pay more to stay at green hotels (Patwary et al, 2022). According to Green Hotel Association (2023), green hotel refers to "environmentally-friendly properties whose managers are eager to institute programs that save water and energy and reduce generation of solid waste -while saving money -to help protect our one and only planet earth. "…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various organizational characteristics influence organizational actors' attitudes toward risk management practice (Fadzil et al 2017), which is also known as risk attitude. The nature of the firm (Brunsson and Olsen 2018), top management influence (Wijethilake and Lama 2019), government impact (Patwary et al 2022b;York et al 2018), organizational actors' knowledge and competence (Zhou et al 2018), and cost of risk management implementation are all factors to consider. In other words, the pressure from the abovementioned elements influences the conduct of organizational actors such as employees responsible for implementing risk management systems.…”
Section: Risk Managementmentioning
confidence: 99%
“…It involves collecting information about specific or general aspects of environmental phenomena [ 45 ] and being aware of the collective responsibilities necessary for green development [ 46 ]. It has been suggested that more knowledge about environmental issues may promote positive attitudes toward the topic [ 44 , 46 , 47 ] and consequently green consumption intention and behavior [ 48 , 49 , 50 ]. A recent study [ 51 ] reported a significant positive relationship between both perceived green knowledge and green trust and customers’ intention to visit green hotels.…”
Section: Introductionmentioning
confidence: 99%